Coarse frame and carrier synchronization of OFDM systems a new metric and comparison. - Kai Shi (IEEE Transactions on wireless communications)
We propose a fast and reduced complexity frame and carrier acquisition scheme for orthogonal frequency-division multiplex systems which assumes either a continuous or a burst mode operation in additive white Gaussian noise and frequency-selective channels. By exploiting the repetitive structure of a training symbol, a robust frame synchronizer is obtained and shown to resume to finding the peak of a certain correlation metric that is obtained by invoking maximum likelihood principles. A modified carrier estimator that can correct frequency offsets up to two subcarrier spacings is also proposed. The efficiency of the proposed synchronization algorithms is illustrated by both theoretical performance analysis and computer simulations.